2015
DOI: 10.1146/annurev-nutr-071714-034410
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fatty Acids and Their Potential for Controlling Metabolic Diseases Through Activation of FFA4/GPR120

Abstract: It is well known that the amount and type of ingested fat impacts the development of obesity and metabolic diseases, but the potential for beneficial effects from fat has received less attention. It is becoming clear that the composition of the individual fatty acids in diet is important. Besides acting as precursors of potent signaling molecules, dietary fatty acids act directly on intracellular and cell surface receptors. The free fatty acid receptor 4 (FFA4, previously GPR120) is linked to the regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 142 publications
(246 reference statements)
0
94
0
1
Order By: Relevance
“…The insulin sensitising and anti-inflammatory actions of GPR120, which is a receptor for n-3 polyunsaturated fatty acids [2][3], is unlikely to be modified by IL-33 contrary to what has been projected with IL-1β and TNFα [7]. The intracellular signalling pathways linked to the IL-33 receptor, ST2 (and its co-receptor IL-1 receptor accessory protein) [15], which are expressed in human adipocytes [11], would appear to be implicated in the modulation of the transcription of the GPR84 gene, but not GPR120.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The insulin sensitising and anti-inflammatory actions of GPR120, which is a receptor for n-3 polyunsaturated fatty acids [2][3], is unlikely to be modified by IL-33 contrary to what has been projected with IL-1β and TNFα [7]. The intracellular signalling pathways linked to the IL-33 receptor, ST2 (and its co-receptor IL-1 receptor accessory protein) [15], which are expressed in human adipocytes [11], would appear to be implicated in the modulation of the transcription of the GPR84 gene, but not GPR120.…”
Section: Discussionmentioning
confidence: 99%
“…Several G-protein coupled receptors act as sensors/receptors for fatty acids [1][2]. GPR120 (or FFAR4), is a receptor for n-3 polyunsaturated fatty acids, and has been linked to the antiinflammatory action of these lipids [2][3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages directly participate in the process of obesity-induced chronic low-grade inflammation, which is tightly associated with macrophage infiltration into peripheral tissues and the pathogenesis of insulin resistance [32,33] . Recent research has indicated that GPR120 plays an important role in energy homeostasis, chronic inflammation and insulin resistance and represents a promising target for obesity and type 2 diabetes (T2DM) therapy [34] . In the present study, LPS-induced production of NO, TNF-α and IL-6 as well as expression of iNOS and COX-2 tended to be reduced by ALA. Incubation with Rb2 prior to ALA treatment dramatically amplified the inhibitory effect of ALA, leading to statistically significantly lower levels of these cytokines and pro-inflammatory enzymes than with ALA treatment alone.…”
Section: Discussionmentioning
confidence: 99%